Plant-Derived Secondary Metabolites as Potential Mediators against COVID-19: A Review - Khanal, Lekha Nath; Pokharel, Yuba Raj; Sharma, Khagaraj; Kalauni, Surya Kanta (Prithvi Academic Journal, 2020)
The current pandemic of COVID-19 caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has envisioned a global health concern. The scientists and physicians around the world have been racing to understand the pathophysiology and possible treatment régimes to discover an effective therapeutic resolution against the disease. Different secondary metabolites from plants exhibit substantial biological assets including antiviral activity. These compounds may be used against the infections of coronavirus. The research papers, reviews, and preprints were searched from the PubMed database using keywords like severe acute respiratory syndrome coronavirus (SARS-CoV), Middle East respiratory syndrome (MERS), and traditional herbal medicine against COVID-19. The review focuses on those natural products which exhibited optimistic results against SARS-COV and SARS-CoV-2 in virtual as well as physical in vitro and in vivo tests. It summarizes the epidemiological characters, pathogenesis, structure, and targeting strategies of the virus. The compounds like lycorine, psoralidin, quercetin, glycyrrhizin, baicalin, caffeic acid, etc. could be the leads for the drug development against COVID-19.